Smart Color Sorting Robot - Siti Nadrah , Selamat (UTeM, 2010)
Smart Color Sorting Robot is based on a placing system with some capability to place the object according to their color. The object will be defined by determining color of the ball while the system will figure out which location the object should be located. With the PIC as a controller for the system, a manually feed object which is a coloring ball will be determined by the robot to take and eject them to their exact location or station. In this project a line follower will brought the ball that will be sense by LDR sensor to right station. A main part in this project is an LDR sensor which is used to detect light. Capability of this system to detect the type of this object and it will be chosen based on their color. There are four stations in the Color Sorter system that we made. Each station had their own range of color except for the first station which is the load and unloading station. The ball will be inserting manually by the user. Then the LDR sensor will detect what color is the object, after the detection been done, the decision will be made and the line follower will take the object to the station that been recognized for it.